Relationship between Tpeak-Tend (TPE), TPE/QT ratio and TPE dispersion in patients with subclinical hyperthyroidism - Bilen, Mehmet Nail; Gozel, Nevzat (My University, 2024)
Aims: Subclinical hyperthyroidism has been associated with an increased risk of cardiovascular events, including atrial fibrillation, heart failure, and cardiovascular mortality. Tpeak - Tend interval (TPE), TPE/QT ratio, and TPE dispersion have been suggested as potential electrocardiographic markers of ventricular repolarization abnormalities, which may be associated with an increased risk of arrhythmias and sudden cardiac death. However, the relationship between subclinical hyperthyroidism and these parameters remains unclear. Methods: We conducted a cross-sectional study to investigate the relationship between subclinical hyperthyroidism and TPE, TPE/QT ratio, and TPE dispersion. A total of 106 patients were included in the study, with 42 patients diagnosed with subclinical hyperthyroidism group and 64 control group. Conventional echocardiographic and electrocardiographic parameters were measured and compared between the two groups. Results: There are no significant differences in age (p=0.707) or gender (p=0.552) between the two groups. Patients in the subclinical hyperthyroidism group had significantly higher TPE, TPE/QT ratio, and TPE dispersion compared to the control group (p<0.001). However, there were no significant differences between the two groups in terms of conventional echocardiographic parameters, including left ventricular (LV) ejection fraction, LV end-diastolic diameter, LV end-systolic diameter, and right ventricular fractional area change. Conclusion: Our results suggest that subclinical hyperthyroidism is associated with increased ventricular repolarization abnormalities, as evidenced by higher TPE, TPE/QT ratio, and TPE dispersion. These findings may have clinical implications for the management of patients with subclinical hyperthyroidism, particularly those with cardiovascular risk factors.
Keywords: Arrhythmia; subclinical hyperthyroidism; ventricular repolarization